Glycolysis and the significance of lactate in traumatic brain injury - Carpenter, Keri L. H.; Jalloh, Ibrahim; Hutchinson, Peter J. (Frontiers in Neuroscience, 2015)
In traumatic brain injury (TBI) patients, elevation of the brain extracellular lactate concentration and the lactate/pyruvate ratio are well recognised, and are associated statistically with unfavourable clinical outcome. Brain extracellular lactate was conventionally regarded as a waste product of glucose, when glucose is metabolised via glycolysis (Embden-Meyerhof-Parnas pathway) to pyruvate, followed by conversion to lactate by the action of lactate dehydrogenase, and export of lactate into the extracellular fluid. In TBI, glycolytic lactate is ascribed to hypoxia or mitochondrial dysfunction, although the precise nature of the latter is incompletely understood. Seemingly in contrast to lactate’s association with unfavourable outcome is a growing body of evidence that lactate can be beneficial. The idea that the brain can utilise lactate by feeding into the tricarboxylic acid (TCA) cycle of neurons, first published two decades ago, has become known as the astrocyte-neuron lactate shuttle hypothesis. Direct evidence of brain utilisation of lactate was first obtained 5 years ago in a cerebral microdialysis study in TBI patients, where administration of 13C-labelled lactate via the microdialysis catheter and simultaneous collection of the emerging microdialysates, with 13C NMR analysis, revealed 13C labelling in glutamine consistent with lactate utilisation via the TCA cycle. This suggests that where neurons are too damaged to utilise the lactate produced from glucose by astrocytes, i.e. uncoupling of neuronal and glial metabolism, high extracellular levels of lactate would accumulate, explaining association between high lactate and poor outcome. An intravenous exogenous lactate supplementation study in TBI patients showed evidence for a beneficial effect judged by surrogate endpoints. Here we review current knowledge about glycolysis and lactate in TBI, how it can be measured in patients, and whether it can be modulated to achieve better clinical outcome.